Effects of Embarrassment on Self-Serving Bias and Behavioral Response in the Context of Service Failure - Hu, Kai-Chieh; Tsai, Hsin-Lin (Behavioral sciences, 2024)
Previous research has focused on examining embarrassment in sensitive product purchase situations. Although embarrassment is a widespread emotion in consumption situations, few studies have explored its impact on service encounters, especially in the service failure context. This study examines how customers react to different service failures that cause embarrassment and explores whether self-serving bias exists when customers perceive higher embarrassment in service failure. This study uses a 2 (source of failure) × 2 (level of embarrassment) scenario experimental method to examine the effect of two sources of failure on consumer locus attributions, negative emotions, and negative behaviors, considering the moderating effects of the level of embarrassment. Data were collected from 218 student subjects in Taiwan. The results show that embarrassment is important in service failure contexts. Specifically, when consumers perceive higher embarrassment, they attribute more responsibility to the service provider. These attributions, in turn, influence customers’ emotions and behavioral responses. These findings have several important theoretical and practical implications in terms of embarrassing service failures.